Revisional notes on Alloea (Hymenoptera: Braconidae: Alysiinae) with a new species for Thailand and detailed English description of Alloea cheni from China - Yao, Junli; Yu, Haiyue (Zootaxa, 2025)
Alloea Haliday, 1383, is a small braconid genus with fifteen previously described species. Alloea is reported from Thailand for the first time, and a new species Alloea doiphukhensis Yao is described and illustrated. Alloea cheni Yao, 2015 from China was originally described in Chinese. Here we give a detailed English description and include color images. A key to Oriental species of Alloea is presented.